Quality and fertility of frozen ovine spermatozoa from epididymides stored at room temperature (18–25 °C) for up to 48 h post mortem - Bergstein-Galan, Tácia Gomes; Weiss, Romildo Romualdo; Bertol, Melina Andrea F.; Abreu, Ana Cláudia M.R.; Busato, Eduarda; Kozicki, Luiz E.; Bicudo, Sony Dimas [UNESP] (Elsevier, 2017)
This study investigates the effect of time of storage of epididymides at room temperature and the addition of 20% of seminal plasma to the cryopreservation extender, on post thaw quality and fertility of ovine spermatozoa collected from the cauda epididymis. Spermatic kinetics, integrity and the stability of plasma membrane, damage to the acrosome and fertility following laparoscopic artificial insemination were evaluated in samples collected in an artificial vagina (AV) and from epididymides stored at room temperature for zero (G0), six (G6), twelve (G12), twenty-four (G24) and forty-eight (G48) hours post mortem. There were no significant differences in spermatic parameters between the methods of sample collection, except for progressive motility and velocity according to the straight path(VSL). G48 samples had significant lower total motility(TM), progressive motility(PM), kinetic parameters, viability and acrosomal integrity. Pregnancy rate after insemination was similar for samples collected using AV, and the G0, G6, G12 and G24 samples. In conclusion, ovine epididymides can be exposed to room temperature, for up to 24 h post mortem, with no effect on viability and fertility of cryopreserved seminal samples. The addition of seminal plasma to the cryopreservation extender had no effect on spermatozoa quality nor fertility.
Keywords: CASA; Epididymis; Seminal plasma